339 A serum exocrine enzyme as a biomarker of response to immunotherapy in type 1 diabetes. (April 2022) - Bruggeman, Brittany S; McGrail, Kieran; Gonzalez, Nicole; Wasserfall, Clive; Campbell-Thompson, Martha; Atkinson, Mark; Haller, Michael; Schatz, Desmond
Abstract : OBJECTIVES/GOALS: We assessed the relationship between C-peptide preservation and a serum exocrine pancreatic enzyme (trypsin) in a recently concluded clinical trial. We hypothesized that immunomodulatory treatment resulting in improved beta-cell function would be associated with improved trypsin levels in subjects with recent-onset type 1 diabetes (T1D). METHODS/STUDY POPULATION: In a three-arm, randomized, double-masked, placebo-controlled trial 'Antithymocyte Globulin (ATG) and pegylated granulocyte colony stimulating factor (GCSF) in New Onset Type 1 Diabetes' 89 subjects with recent-onset T1D (duration <100 days) were enrolled and randomized to 3 groups: low-dose ATG (2.5 mg/kg IV) followed by pegylated GCSF (6 mg subcutaneously every 2 weeks for 6 doses), low-dose ATG alone, and placebo. We compared longitudinal serum levels of an exocrine enzyme (trypsin) in a subset of responders to therapy (defined as subjects with at least 60% of baseline area under the curve (AUC) C-peptide levels at 96 weeks, n=4) versus placebo 'responders' (n=2) and non-responders (n=25), and treated (n=19) versus placebo (n=12) subjects at baseline, 2 weeks, and 6 months after treatment. RESULTS/ANTICIPATED RESULTS: There was no observed difference in treated (n=20) versus placebo (n=12) longitudinal trends in trypsin levels when compared to baseline levels. However, responders to immunotherapy (n=4) had 6 month trypsin levels that were 114% of baseline whereas placebo subject 'responders' (n=2), placebo subjects (n=10), and non-responders to immunotherapy (n=15) had trypsin levels that were 81-93% of baseline (unpaired T test p=0.05). Overall, we found that serum trypsin, a marker of exocrine pancreatic function, had a normal upward trend in new-onset T1D subjects who responded clinically to immunotherapy but declined in subjects who did not respond or who were not treated. These results were bordering on statistical significance but did not reach significance, likely due to the small sample size. DISCUSSION/SIGNIFICANCE: An improvement in trypsin, a marker of exocrine function, after response to immunotherapy in new-onset T1D may be due to a direct impact on exocrine function versus an indirect effect from improved beta cell function. Future studies will be needed to confirm our findings in a larger sample and evaluate the mechanism for improved exocrine function.